FAKTOR YANG BERHUBUNGAN DENGAN POLA MENYUSUI BAYI DAN ANAK USIA 6-23 BULAN DI INDONESIA - Widodo, Yekti; Sandjaja, Sandjaja (PERSATUAN AHLI GIZI INDONESIA, 2015)
ABSTRACT Exclusive breastfeeding for the first 6 months after birth and continued breastfeeding for up to 2 years is a very beneficial. The objectives of the study were to get better insight on the proportion of breastfeeding and its associated factors among Indonesian children to support breastfeeding awareness program. SEANUTS was a multi-centered nutrition study conducted in Indonesia, Malaysia, Thailand, and Vietnam. A subsample of 2.391 Indonesian children 6-23 months of age was analyzed using ANCOVA and multiple logistic regression. The results showed that 4.5 percent of the children were never breastfed. The study showed that factors significantly associated with never being breastfed were child not lived with his/her mother (OR = 5,0), mother’s education was junior high school or less (OR = 2,7), and child caregiver was not his/her mother (OR = 3,27). Delivery helped by private health practitioner or at home was significantly protective against not being breasfed (OR = 0,37). The overall proportion of children 6-23 months of age still being breastfed was 73.3 percent. Factors significantly associated with weaning were early weaned (OR = 1,13), working mother (OR = 2,0), child caregiver not his/her mother (OR = 1,62), and not lived with his/her mother (OR = 9,35). Factors associated with longer breastfeeding were living in rural areas (OR = 0,69), older age of mother 30-39 years (OR = 0,67), delivery at home (OR = 0,45) or health practitioner (OR = 0,65). In conclusion, the research indicated that not all babies get breastfeed in an optimal level. Health promotion program to increase breastfeeding awareness should be targeted more for health profesionals in hospital and maternity clinics, mother’s education was at junior high school or less, young mother, and in the urban area. Keywords: breastfeeding, weaning, Indonesian children ABSTRAK Menyusui eksklusif selama 6 bulan dan dilanjutkan pemberian ASI sampai anak usia 2 tahun, terbukti sangat bermanfaat. Tujuan penelitian adalah menganalisis faktor yang berhubungan dengan pola menyusui guna mendukung program menyusui di Indonesia. Data merupakan subsampel penelitian SEANUTS Indonesia yaitu anak 6-23 bulan berjumlah 2391. SEANUTS merupakan multi-centered study yang dilakukan di Indonesia, Malaysia, Thailand, dan Vietnam pada tahun 2011. Analisis data dilakukan secara deskriptif dan diuji statistik dengan ANCOVA dan multiple logistic regression. Hasil penelitian menunjukkan proporsi anak yang tidak pernah mendapat ASI adalah 4,5 persen. Hasil analisis menunjukkan faktor yang berhubungan dengan perilaku tidak menyusui yaitu tidak tinggal dengan ibu (OR = 5,0), pendidikan ibu SMP ke bawah (OR = 2,7), tidak diasuh oleh ibu kandung (OR = 3,27). Persalinan di klinik bidan atau di rumah bersifat protektif terhadap perilaku tidak menyusui (OR = 0,37). Proporsi anak usia 6-23 bulan yang masih disusui adalah 73,3 persen. Faktor yang berhubungan dengan disapih lebih awal adalah (OR = 1,13), ibu bekerja (OR = 2,0), pengasuh bukan ibu (OR = 1,62), dan anak tidak tinggal dengan ibu (OR = 9,35). Faktor yang berhubungan dengan durasi menyusui lebih lama adalah tinggal di perdesaan (OR = 0,69), umur ibu 30-39 tahun (OR = 0,67), persalinan di rumah (OR = 0,45), di klinik bidan (OR = 0,65). Penelitian ini menunjukkan tidak semua bayi mendapat ASI secara optimal. Target program promosi kesehatan untuk meningkatkan pemberian ASI sampai usia 2 tahun adalah petugas kesehatan di rumah sakit, orang tua bayi berpendidikan SMP ke bawah, ibu usia muda, dan di daerah perkotaan.